The Effect of the Problem-Based Learning Model Based on the Science, Technology, Engineering, and Mathematics (STEM) Approach on Students' Creative Thinking Ability - Nenni Sara; Pinta Murni; Syamsurizal Syamsurizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This research aims to analyze the effect of the Problem-Based Learning (PBL) model based on the STEM approach on students' creative thinking ability in the topic of the plant reproductive system. The design used was a quasi-experiment with a pretest-posttest control group model. The population consisted of all Grade IX students of MTS Laboratorium Jambi, totaling 120 students, while the sample comprised 48 students, consisting of Class IX-D and Class IX-E. The instruments used were an essay test of creative thinking ability and a student response questionnaire toward the Problem-Based Learning Model based on STEM. The initial data analysis techniques used the normality test, homogeneity test, and hypothesis test, while the final data analysis techniques used the N-Gain test and analysis of creative thinking ability data. The results of the analysis of creative thinking ability showed an N-Gain score of 0.57 in the experimental class, which is categorized as moderately effective, while the control class obtained an N-Gain score of 0.44, which is categorized as less effective. The PBL Model Based on STEM had a moderate effect on creative thinking ability. Based on the research findings, the dominant indicator of creative thinking was originality, which was moderately effective, while flexibility was found to be effective